Ultra-deep sequencing improves the detection of drug resistance in cellular DNA from HIV-infected patients on ART with suppressed viraemia. (20th August 2018) - Rodriguez, Christophe; Nere, Marie Laure; Demontant, Vanessa; Charreau, Isabelle; Mercier-Darty, Mélanie; Delagreverie, Héloïse; Salmona, Maud; de Castro, Nathalie; Chaix, Marie Laure; Molina, Jean Michel; Delaugerre, Constance
Abstract: Background: Standard genotypic tests performed on HIV DNA from patients on suppressive ART, with previous resistance-associated mutations (RAMs) detected in their plasma, underestimate resistance. We thus compared ultra-deep sequencing (UDS) with bulk sequencing of DNA to detect RAMs previously identified in plasma. Methods: We sequenced the DNA of 169 highly treatment experienced patients with suppressed viraemia (ANRS 138-EASIER trial). Protease (PR) and reverse transcriptase (RT) genes from HIV DNA were sequenced by bulk sequencing and UDS, comparing 1% and 20% as thresholds of detection for UDS. Results: Patients were highly treatment experienced (13.6 years). UDS of DNA was successful for the RT and PR genes in 133 (79%) and 137 (81%) patients, respectively. The detection of RAMs was similar by bulk sequencing and UDS with a 20% cut-off. However, the detection of RAMs by UDS with a 1% cut-off was significantly higher than that of bulk sequencing for RT codons D67N (65.4% versus 52.3%), M184V (66.2% versus 52.3%), L210W (48.9% versus 36.4%) and T215Y (57.9% versus 42.1%) and PR codons M46I (46% versus 26%), I54L (12.4% versus 3.9%), V82A (44.5% versus 29.9%) and L90M (57.7% versus 42.5%). Conclusions: Genotypic resistance testing of cellular HIV DNA of well-controlled patients should use UDS technology with a sensitivity threshold of 1% to improve the detection of the resistant reservoir.